CoO/MnO heterostructure on three-dimensional nickel foam as efficient electrocatalyst for oxygen evolution reaction. (January 2022) - Lin, Yanna; Yang, Guijin; Fu, Yujun; Zhu, Botao; Zhao, Jing; Li, Jinyun
Abstract: At present, transition metal oxides are the most potential electrocatalytic materials. However, its poor conductivity and few active sites hinder its development in various fields. Therefore, the CoO/MnO heterostructures with abundant oxygen vacancies were prepared on the three-dimensional nickel foam by hydrothermal and vacuum annealed methods. Electrochemical studies reveal that Co:Mn = 1:1@NF has superior electrocatalytic performance with overpotential of 280 mV at current density of 10 mA cm −2 and Tafel slope of 46.6 mV dec −1 in 1 M KOH. As well, the CoO/MnO heterostructures presents predominant stability for over 25 h. The excellent OER performance of the Co:Mn = 1:1@NF is mainly attributed to the abundant heterostructures, oxygen vacancies and unique porous structure of nanowires and nanosheets. Therefore, this research offers a new idea for the reasonable design of low-cost electrocatalysts. Highlights: The unique heterostructure catalyst of Co:Mn = 1:1@NF showed a low overpotential of 280 mV at 10 mA cm −2 for OER activity. The electronic reorganization and abundant oxygen vacancies provide excellent OER performance and stability. The choice of abundant and cheap MnO offers a new direction for interface engineering.